Diffusion tensor imaging of articular cartilage using a navigated radial imaging spin-echo diffusion (RAISED) sequence. - Duarte, Alejandra; Ruiz, Amparo; Ferizi, Uran; Bencardino, Jenny; Abramson, Steven B.; Samuels, Jonathan; Krasnokutsky-Samuels, Svetlana; Raya, José G. (European Radiology, 2019)
Objective: To validate a radial imaging spin-echo diffusion tensor (RAISED) sequence for high-resolution diffusion tensor imaging (DTI) of articular cartilage at 3 T.Methods: The RAISED sequence implementation is described, including the used non-linear motion correction algorithm. The robustness to eddy currents was tested on phantoms, and accuracy of measurement was assessed with measurements of temperature-dependent diffusion of free water. Motion correction was validated by comparing RAISED with single-shot diffusion-weighted echo-planar imaging (EPI) measures. DTI was acquired in asymptomatic subjects (n = 6) and subjects with doubtful (Kellgren-Lawrence [KL] grade 1, n = 9) and mild (KL = 2, n = 9) symptomatic knee osteoarthritis (OA). MD and FA values without correction, and after all corrections, were calculated. A test-retest evaluation of the DTI acquisition on three asymptomatic and three OA subjects was also performed.Results: The root mean squared coefficient of variation of the global test-restest reproducibility was 3.54% for MD and 5.34% for FA. MD was significantly increased in both femoral condyles (7-9%) of KL 1 and in the medial (11-17%) and lateral (10-12%) compartments of KL 2 subjects. Averaged FA presented a trend of lower values with increasing KL grade, which was significant for the medial femoral condyle (-11%) of KL 1 and all three compartments in KL 2 subjects (-18 to -11%). Group differences in MD and FA were only significant after motion correction.Conclusion: The RAISED sequence with the proposed reconstruction framework provides reproducible assessment of DTI parameters in vivo at 3 T and potentially the early stages of the disease in large regions of interest.Key Points: • DTI of articular cartilage is feasible at 3T with a multi-shot RAISED sequence with non-linear motion correction. • RAISED sequence allows estimation of the diffusion indices MD and FA with test-retest errors below 4% (MD) and 6% (FA). • RAISED-based measurement of DTI of articular cartilage with non-linear motion correction holds potential to differentiate healthy from OA subjects.